What Goes on in This House Do Not Stay in This House: Family Variables Related to Adolescent-to-Parent Offenses - Hernández, Antonia; Martín, Ana M.; Hess-Medler, Stephany; García-García, Juan (Frontiers in Psychology, 2020)
Research on adolescent-to-parent violence (APV) associates specific psychosocial characteristics with adolescents who assault their parents, whether they are within or outside the juvenile justice system, or whether these characteristics are shared by other adolescents convicted of other crimes. The aim of this paper is to compare three groups of adolescents. Those who have been sentenced for APV are compared with adolescents who have committed other crimes, and with a group who have not been involved in the justice system. The sample used consists of 148 male participants between the ages of 14 and 21. A comparison is made regarding type of self-reported behavior, frequency of drug use, academic performance, exposure to violence, self-concept and parents’ conflict resolution tactics. The results obtained indicate that adolescents with judicial measures, regardless of the crime committed, differ from those who have not been in trouble with the justice system in terms of them having suffered violence in the street, in the frequency with which they use drugs and in their academic achievement. Likewise, adolescents convicted of APV differ from the other two groups in the frequency with which they are victims of violence at home, in that their mothers use the tactic of asking somebody else for help as a way of solving marital conflicts, and in having a more negative family self-concept. The results are discussed highlighting the importance of taking into account whether a sample is judicial, clinical or community, and the specific APV behaviors which are measured.